Evaluating Accuracy of DNA Pool Construction Based on White Blood Cell Counts - Abrams, Amy N.; McDaneld, Tara G.; Keele, John W.; Chitko-McKown, Carol G.; Kuehn, Larry A.; Gonda, Michael G. (Frontiers in Genetics, 2021)
Pooling individual samples prior to DNA extraction can mitigate the cost of DNA extraction and genotyping; however, these methods need to accurately generate equal representation of individuals within pools. The objective of this study was to determine accuracy of pool construction based on white blood cell counts compared to two common DNA quantification methods. Fifty individual bovine blood samples were collected, and then pooled with all individuals represented in each pool. Pools were constructed with the target of equal representation of each individual animal based on number of white blood cells, spectrophotometric readings, spectrofluorometric readings and whole blood volume with 9 pools per method and a total of 36 pools. Pools and individual samples that comprised the pools were genotyped using a commercially available genotyping array. ASReml was used to estimate variance components for individual animal contribution to pools. The correlation between animal contributions between two pools was estimated using bivariate analysis with starting values set to the result of a univariate analysis. Adonis test on distance matrix from the animal correlation showed clustering with method, and higher correlations between methods than within (P < 1 × 10-6). White blood cell count was predictive of sample representation when compared to pooling based on DNA concentration. Therefore, constructing pools using white blood cell counts prior to DNA extraction may reduce cost associated with DNA extraction and genotyping and improve representation of individuals in a pool.